Semi‐volatile organic compounds in the air and dust of 30 French schools: a pilot study. (16th March 2016) - Raffy, G.; Mercier, F.; Blanchard, O.; Derbez, M.; Dassonville, C.; Bonvallot, N.; Glorennec, P.; Le Bot, B.
Abstract: The contamination of indoor environments with chemical compounds released by materials and furniture, such as semi‐volatile organic compounds (SVOCs), is less documented in schools than in dwellings—yet children spend 16% of their time in schools, where they can also be exposed. This study is one of the first to describe the contamination of the air and dust of 90 classrooms from 30 nursery and primary schools by 55 SVOCs, including pesticides, phosphoric esters, musks, polycyclic aromatic hydrocarbons (PAHs), polychlorobiphenyls (PCBs), phthalates, and polybromodiphenylethers (PBDEs). Air samples were collected using an active sampling method, and dust samples were collected via two sampling methods (wiping and vacuum cleaning). In air, the highest concentrations (median >100 ng/m 3 ) were measured for diisobutyl phthalate (DiBP), dibutyl phthalate (DBP), diethyl phthalate (DEP), bis(2‐ethylhexyl) phthalate (DEHP), and galaxolide. In dust, the highest concentrations (median >30  μ g/g) were found for DEHP, diisononyl phthalate (DiNP), DiBP, and DBP. An attempt to compare two floor dust sampling methods using a single unit (ng/m²) was carried out. SVOC concentrations were higher in wiped dust, but frequencies of quantification were greater in vacuumed dust.